The integrative role of cryo electron microscopy in molecular and cellular structural biology. (25th November 2016) - Orlov, Igor; Myasnikov, Alexander G.; Andronov, Leonid; Natchiar, S. Kundhavai; Khatter, Heena; Beinsteiner, Brice; Ménétret, Jean‐François; Hazemann, Isabelle; Mohideen, Kareem; Tazibt, Karima; Tabaroni, Rachel; Kratzat, Hanna; et al.
Abstract : Review : In this paper, we review latest advances in cryo electron microscopy (cryo‐EM) which allow unprecedented high‐resolution analysis thanks to new detector instrumentation leading to a revolution in resolution in the cryo‐EM field. These latest technological developments underline the role of cryo‐EM in multi‐scale multi‐resolution integration, thus bridging cellular scales and atomic details in synergy with other methods such as X‐ray crystallography, fluorescence imaging or focussed‐ion beam milling. This illustrates the trend of the field towards cellular structural biology. Abstract : After gradually moving away from preparation methods prone to artefacts such as plastic embedding and negative staining for cell sections and single particles, the field of cryo electron microscopy (cryo‐EM) is now heading off at unprecedented speed towards high‐resolution analysis of biological objects of various sizes. This 'revolution in resolution' is happening largely thanks to new developments of new‐generation cameras used for recording the images in the cryo electron microscope which have much increased sensitivity being based on complementary metal oxide semiconductor devices. Combined with advanced image processing and 3D reconstruction, the cryo‐EM analysis of nucleoprotein complexes can provide unprecedented insights at molecular and atomic levels and address regulatory mechanisms in the cell. These advances reinforce the integrative role of cryo‐EM in synergy with other methods such as X‐ray crystallography, fluorescence imaging or focussed‐ion beam milling as exemplified here by some recent studies from our laboratory on ribosomes, viruses, chromatin and nuclear receptors. Such multi‐scale and multi‐resolution approaches allow integrating molecular and cellular levels when applied to purified or in situ macromolecular complexes, thus illustrating the trend of the field towards cellular structural biology.